PERISTIWA FITNAH KUBRO: SEJARAH DAKWAH YANG HARUS DILURUSKAN - Rahmat Hidayat; Daud Rasyid; Riska Ramdani; Rambang Basari; Retna Dwi Estuningtyas (Al-Idaroh: Media Pemikiran Manajemen Dakwah, 2025)
The Fitnah al-Kubra is one of the most tragic events in Islamic history and is the primary cause of sectarian divisions among Muslims. The term "fitnah" in this context refers to the trials and tribulations that occurred after the death of the Prophet Muhammad, which triggered conflicts among the companions and the Muslim community. The climax of this event occurred with the outbreak of civil war during the reigns of Caliphs Uthman ibn Affan and Ali ibn Abi Talib, both of whom were killed. This division resulted in two major sects in Islam: Sunni and Shia, with deep-rooted political differences. Sectarianism in Islam, understood as a system of attitudes and practices that utilizes religious differences as a marker of social boundaries, has been defined by scholars such as Adib Abdulmajid, Liechty, Clegg, and Brewer. This phenomenon of sectarianism is not only prevalent in the Middle East but is also evident in the context of other Muslim countries, including Indonesia, which has the largest Muslim population in the world. This research will further examine the roots and impacts of sectarian conflict in the history and modern life of the Muslim community.